Physicochemical characterization of composts for the cultivation of Pleurotus ostreatus - Zanon, André Ricardo [UNESP]; De Jesus, João Paulo Furlan [UNESP]; Vieira, Fabrício Rocha [UNESP]; Martins, Olívia Gomes [UNESP]; De Andrade, Meire Cristina Nogueira [UNESP] (Centro Universitario de Maringa, 2019)
Pleurotus ostreatus var. Florida is one of the main varieties of mushroom that is expanding in the Brazilian market. In Brazil, the most widely used method to obtain the cultivation substrate is the short composting with subsequent steam pasteurization and conditioning. Nevertheless, there is not a standard procedure related to the preparation of substrate adopted by Brazilian mushroom producers, therefore it becomes relevant to find out through research a more efficient method in which producers may back themselves up. Thus, tests were carried out in three different composting periods (T1= 6 days, T2= 4 days and T3=2 days) corresponding to three treatments. The experiment occurred between August and October 2013 by relating the physical and chemical characteristics of the composts with the mushroom production parameters. Treatments T1 and T2 presented the best results regarding biological efficiency (T1=108.91% and T2=102.49%, respectively) and productivity (T1=26.22% and T2=25.72 %), as well as a higher number of harvested mushrooms (T1=44.44 and T2=43.52). These treatments presented the best results mainly due to a lower C/N ratio (T1=47 and T2=46) and a higher amount of crude protein (6.61% and 6.52%) available for the compost at the end of Phase II. These two periods of composting also influenced the mushroom cellulose and hemicellulose consumption by the fungus. Therefore, composting influences the production of P. ostreatus var. Florida.
Keywords: Biological efficiency; Composting; Oyster mushroom; Shimeji; Sugar cane